0325 A Comprehensive Evaluation of Sleep Disorders in Male and Female U.S. Military Personnel. (25th May 2022) - Mysliwiec, Vincent; Brock, Matthew; Pruiksma, Kristi; Straud, Casey; Taylor, Daniel; Hansen, Shana; Foster, Shannon; Zwetig, Sarah; Gerwell, Kelsi; Young-McCaughan, Stacey; Powell, Tyler; Star, John Blue; et al.
Abstract: Introduction: Sleep disorders are increasingly recognized in military personnel. However, no study has comprehensively evaluated male and female service members with clinically significant sleep disturbances. While, insomnia and obstructive sleep apnea (OSA) are the two most recognized sleep disorders, some studies have suggested that comorbid insomnia and OSA, also known as COMISA, potentially is the most frequent sleep disorder. Further little is known regarding the co-occurrence of nightmares, shift work disorder, depression, anxiety, and posttraumatic stress disorder (PTSD) in this population. Methods: Participants were 309 active duty service members (females n = 113, male n = 196) in all branches of the military who underwent a clinically indicated sleep evaluation in a military sleep disorders center. All underwent an attended in-lab polysomnogram, were diagnosed with insomnia, OSA, or COMISA and completed self-report measures. Participants completed the Nightmare Disorder Index and Shift Work Disorder Index, and non-sleep questionnaires using the PCL-5 for post-traumatic stress disorder (PTSD), the PHQ-9 for depression, the GAD-7 for anxiety, and History of Head Injuries for traumatic brain injury (TBI). Results: COMISA was diagnosed in 36.8% of the sample, insomnia in 32.7%, and OSA in 30.4%. Males were significantly more likely to have COMISA or OSA and females were more likely to have insomnia. Polysomnographic variables were consistent with the respective sleep diagnoses. Forty service members (12.9%) met criteria for nightmare disorder; those with OSA were significantly less likely to have nightmares. Shift work disorder was present in 49 (15.9%) and did not differ between sleep diagnoses. PTSD was present in 57 (18%) and those with COMISA were significantly more likely to have PTSD. A history of head injuries was reported by 38.2% and there was no difference in rates between the sleep disorder groups. Conclusion: The most frequent sleep disorder profile in service members with sleep disturbances was COMISA, which was associated with significantly higher rates of PTSD and anxiety. Conversely, OSA alone was not associated with higher rates of any comorbid disorders. Nightmare disorder and shift work are relatively prevalent in military personnel with sleep disorders. Support (If Any): This work was supported by the Defense Health Agency, Defense Medical Research and Development Program, Clinical Research Intramural Initiative for Military Women's Health (DM170708; Mysliwiec), and the Air Force Research Laboratory, Wright Patterson Air Force Base, Ohio (FA8650-18-2-6953; Peterson). The views expressed herein are solely those of the authors and do not represent an endorsement by or the official policy or position of the U.S. Air Force, the U.S. Army, the Defense Health Agency, the Department of Defense, the Department of Veterans Affairs, or the U.S. Government.